Penentuan Karakteristik Batubara Berdasarkan Analisis Proksimat pada PT Tribhakti Inspektama Kabupaten Tanah Bumbu Kalimantan Selatan - Dzakir, La Ode; Aldiyansyah; Heriansyah, Andi Fahdli (Jurnal of Mining Insight, 2023)
The role of coal as a substitute energy source for oil and gas is getting bigger, especially to increase the pace of development and economic growth. Therefore, Indonesia's coal production and consumption will continue to be increased, especially as direct fuel for power plants, large and medium-sized industries, and home industries. The purpose of this research is to study the characteristics of coal based on proximate analysis while the purpose of this research is to determine the quality of coal based on proximate analysis. The results of the analysis on coal carried out at the PT Tribhakti Inspektama laboratory regarding proximate analysis in the Batu Licin sub-district, Tanah Bumbu Regency, South Kalimantan for moisture, the average value of the 6 samples obtained 18,72% results using the formula that has been determined, the average value for ash analysis was 3,30%, the total average value for volatile matter was 41.02% and for fixed carbon based on the results of analysis in the laboratory the average value was 36.97% then, from the analysis results when compared with the table regarding coal classification according to ASTM, coal in the Batu Licin sub-district, Tanah Bumbu Regency, South Kalimantan is included in the quality of lignite and from the test results the coal can meet the requirements for the cement and metal industry.